Pengembangan industri pengolahan sagu skala rumah tangga di Kabupaten Teluk Wondama Provinsi Papua Barat: Development of home industry sago processing in Teluk Wondama Regency, West Papua Province - Darma Darma; Reniana Reniana; Budi Santoso; Bertha Mangallo (Fakultas Peternakan Universitas Papua, 2023)
ABSTRACTÂ Development of small scale of sago processing based on community in West Papua Province has a bright prospect because it is supported by abundant sago palm resources as row material. Teluk Wondama is one of the regency in West Papua Province which has high potential of sago, unfortunately the potency have not utilized optimally. The ovjective of this program was to develop home industry sago processing in Distric Rasiei, Teluk Wondama Regency by application of mechanical sago processing machines. The methods used were introducing mechanical sago processing equipment followed by partner training and assistance to operate the machines for sago starch production. The results had been achieved from this program were (1) partner have new asset i.e. a set of sago processing equipment which consists of sago rasping machine variant-01 and stirrer rotary blade type of sago starch extraction machine, as well as supporting components such as starch sedimentation tank and water pump (2) partner have already changed their method in sago processing, from traditional method to mechanical one, (3) partner were able to operate the machine easily without any difficulties. During training and assistance, the machine was work properly and there was no technical constrains (4) fresh sago starch production capacity increase from 352 kg/week to 2.112 kg/week. Keywords: Home industry; Sago processing machine; Sago rasping machine; Teluk wondama Â ABSTRAK Papua Barat memiliki prospek yang cerah karena didukung bahan baku yang melimpah berupa sumberdaya sagu. Teluk Wondama merupakan salah satu kabupaten di Papua barat dengan potensi sagu yang tinggi namun belum dimanfaatkan secara optimal. Tujuan dari program ini adalah untuk mengembangkan pengolahan sagu skala industri rumah tangga melalui penerapan mesin pengolahan mekanis di Distrik Rasiei, Kabupaten Teluk Wondama. Metode yang digunakan adalah mengintroduksi peralatan pengolahan sagu mekanis diikuti dengan pelatihan dan pendampingan mitra dalam pengoperasian mesin untuk produksi sagu. Hasil yang dicapai adalah (1) mitra memiliki asset baru berupa 1 paket mesin pengolahan sagu yang terdiri dari mesin parut sagu tipe silinder variant-01 dan mesin ekstraksi pati sagu tipe stirrer rotary blade beserta bagian pendukung berupa bak pengendapan pati dan pompa air, (2) mitra telah merubah metode pengolahan sagu dari cara tradisional ke mekanis, (3) mitra telah terampil mengoperasikan mesin-mesin pengolahan yang diintroduksi dan selama kegiatan berlangsung mesin berfungsi dengan baik tanpa kendala teknis, (4) kapasitas produksi pati sagu meningkat dari 352 kg/minggu menjadi 2.112 kg/minggu. Kata kunci: Industri rumah tangga; Mesin pengolahan sagu; Pemarut sagu; Teluk wondama